LEGAL BASIS OF RELATIONS BETWEEN RELIGIOUS ORGANIZATIONS AND CIVIL SOCIETY INSTITUTES (American Journal of Pedagogical and Educational Research, 2025)
This article discusses the relations between the state, religion, and religious organizations , the lawful activities of religious organizations , the need to improve their role within the system of civil society institutions , the procedure for establishing religious organizations under the legislation of the Republic of Uzbekistan; and the content and key directions of the state policy in the religious sphere and the concept of ensuring citizens' freedom of conscience in the Republic of Uzbekistan.